Potential of rooftop solar electric energy on campus buildings high school of technology Sinar Husni using helioscope software - Ahmad Dani; Dino Erivianto (Jurnal Info Sains : Informatika dan Sains, 2024)
This research is directed at analyzing the potential of electrical energy from Rooftop Solar Power Plants in the Sinar Husni College of Technology Campus Building, with the utilization of Helioscope software. This research is the basis for understanding the extent of solar energy potential that can be generated by solar power plants in the STT Sinar Husni campus building. The method used involves reviewing literature related to solar energy, Solar Power Plants, and the use of Helioscope as analysis software. The location of this research is the Sinar Husni College of Technology Campus Building. The process of retrieving solar radiation data for one year from the meteonorm website was carried out by accessing the meteonorm web platform. In this study, a monocrystalline solar module with a capacity of 320 Wp was used. By utilizing the Google Earth application, information was generated that the area available for the installation of solar modules is 270 m2. To determine the right number of PV modules according to the desired design, Helioscope software was used. The calculation results show that the building can accommodate the installation of 77 solar panels. Solar Radiation / Irradiance: The solar radiation received at this location, expressed in kWh/m2, reached 1,466.3 kWh/m2 in one year. Power Generated by Solar Panels: The solar panel type Trina Solar, model TSM-PD14 320 (May16) (320W) in one year reached 31,248.5 kWh.